Relationship among local and functional factors in the development of denture stomatitis in denture wearers in northern Brazil - GAUCH,Lurdete Maria Rocha (2014)
OBJECTIVE: The aim of this study was to evaluate the relationship among functional and qualitative factors in the development of denture stomatitis (DS) (according to Newton's classification) in acrylic-based denture wearers residents from northern Brazil.MATERIAL AND METHOD: A total of 99 patients who wore partial or total acrylic resin-based upper dentures were included in this study. The subjects completed an epidemiological data form that includes the patient's gender, age, local factors (hygiene habits, remove denture to sleep, use of mouthwash, present condition of the denture, age of the denture) and functional factors (vertical dimension at rest, vertical dimension of occlusion, occlusion, retention, and static and dynamic stability). To detect yeasts, samples were collected from the inner surface of the dentures and from the palatal mucosa in contact with it. Subsequently, the samples were cultured on Sabouraud dextrose agar, observing macro and microscopic characteristics.RESULT: In the present study, we did not find any significant relationship between the gender and disease onset. Based on the Newton classification, 36.3% of the patients presented with DS and 89.0% were colonized by yeasts; of these subjects, 50% had type I lesions, 33.3% had type II lesions, and 16.6% had type III lesions. All of the qualitative and local factors, except the use of mouthwash, were clinically relevant to the development of disease.CONCLUSION: Denture stomatitis in denture users in northern Brazil was multifactorial, involving local, functional and microbiological factors.